2021
DOI: 10.1111/nyas.14555
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents steroid‐induced osteonecrosis of the femoral head via miR‐146a modulation

Abstract: The purpose of this study was to investigate the possible use of resveratrol (Res) to reverse abnormal osteogenesis/osteoclastogenesis activity that occurs during femoral head osteonecrosis and to explore the detailed mechanisms. Application of Res to bone marrow–derived mesenchymal stem cells in vitro promoted survival, inhibited apoptosis, and downregulated expression of reactive oxygen species expression. Moreover, Res application was associated with elevated microRNA‐146a (miR‐146a) expression, osteogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Protein levels are determined as previously described (Nan, Pei, et al, 2021). Cell and tissue samples were lysed in radio‐immunoprecipitation assay buffer and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…Protein levels are determined as previously described (Nan, Pei, et al, 2021). Cell and tissue samples were lysed in radio‐immunoprecipitation assay buffer and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…Another debated one is miR-146a, which was reported to be engaged in both promoting and inhibiting osteoblastic apoptosis. 74,75 Cao et al demonstrated that the expression of caspase-3 and Bax could be inhibited by downregulation of miR-146a. Thus, making use of the competitive endogenous RNA (ce-RNA) mechanism of circRNA–Rtn4 to sponge miR-146a can significantly attenuate apoptosis in osteoblasts.…”
Section: Mirna-mediated Regulation Of Distinct Death Patterns Of Oste...mentioning
confidence: 99%
“…75 Differently, Nan et al reported that miR-146a could protect against steroid-induced osteonecrosis. 74 They showed that miR-146a down-regulated the ROS levels and protected bone trabecular structures via down-mediating the Wnt/FOXO signaling pathway.…”
Section: Mirna-mediated Regulation Of Distinct Death Patterns Of Oste...mentioning
confidence: 99%
“…79,80 Nan et al investigated the effect of resveratrol on the abnormal bone formation and osteoclastogenic activity that occurs in the pathogenesis of steroid-induced femoral head necrosis. 65 Application of resveratrol to BMSCs in vitro inhibited apoptosis, promoted survival, and downregulated the expression of reactive oxygen species. In addition, resveratrol was associated with osteogenic differentiation and increased microRNA-146a expression, suggesting that resveratrol may prevent ONFH.…”
Section: Feng Et Al Investigated the Underlying Mechanisms Accounting...mentioning
confidence: 99%
“…Resveratrol is a polyphenol compound found in various types of natural fruits and plants, has antioxidant properties 79,80 . Nan et al investigated the effect of resveratrol on the abnormal bone formation and osteoclastogenic activity that occurs in the pathogenesis of steroid‐induced femoral head necrosis 65 . Application of resveratrol to BMSCs in vitro inhibited apoptosis, promoted survival, and downregulated the expression of reactive oxygen species.…”
Section: Preclinical In Vitro Studiesmentioning
confidence: 99%